Middle and Late Miocene Cricetidae (Rodentia, Mammalia) from Denizli Basin (Southwestern Turkey) and a New Species of Megacricetodon. (May 2014) - Erten, Hüseyin; Sen, Sevket; Görmüş, Muhittin
Abstract : The occurrences of Cricetidae and the description of a new species, Megacricetodon yenicekentensis new species from the Denizli terrestrial Neogene Basin are considered herein. The Miocene sediments of the area mainly include terrestrial siliciclastic sediments and have a significant mammal fauna. Fieldwork was carried out in the six localities in the basin and the following rodents were identified: Cricetodon candirensis, Cricetulodon hartenbergeri, Megacricetodon minor and Megacricetodon yenicekentensis n. sp. This is the first study of rodent faunas from the Denizli Basin, which is still poorly documented. This study contributes to a better understanding of the stratigraphic and geological features of the Denizli Basin, which is one of the grabens formed within the Neotectonic period of Western Anatolia and has a significant role in explaining the tectonic evolution of the region. Its sedimentary units are, in stratigraphic order, the Kızılburun, Sazak, Kolankaya and Ulubey formations. Based on the systematics and biochronological implications of cricetids and the bulk faunas from six localities, the time range of these formations is discussed, and an age between the early middle Miocene (MN 6) and late Miocene (MN 10) is proposed for this stratigraphic succession. In addition, the dating of the Ulubey Formation, which is observed both in the Denizli and Uşak-Selendi basins, provides new data about the time of connection between these two basins.